Ecological Restoration and Renovation of Xin River Based on Sponge City Concept - He, Shichang (International Journal of Natural Resources and Environmental Studies, 2024)
China is currently facing various water problems such as water scarcity, water pollution, floods, and loss of aquatic habitats. These water problem syndromes are systemic and comprehensive problems that urgently require a more comprehensive solution. The proposal of the "Sponge City" theory is based on this background. According to Jiaozuo "7.20 extremely heavy rainstorm Event", based on the sponge city theory, citing ecological principles, and following ecological principles, this paper discusses the ecological transformation of the Xin River to achieve the purpose of artificially rebuilding the river ecosystem.